(untitled) (Bioscience Journal, 2022)
Organic fertilizers increase soil aeration, water and nutrient holding capacity, improve seed germination and encourage the production of thicker roots, increase the yield and quality of the crop. This study was aimed to determine the effects of organic fertilizer (vermicompost, sheep manure, cattle manure, poultry manure and inorganic fertilizer as control) applications on the root and plant development of soybean during two growth stages, namely third trifoliate stage (V3) and beginning of flowering of the plants (R1) in the pot condition. The experiment was established with a two-factorial randomized plot design with four replications. The fertilizer applications had a significant effect (p<0.01) on the V3 and R1 growth stages of soybean. The highest plant height (36.78 cm) and root length (41.18 cm) were achieved with vermicompost, and the lowest plant height (21.73 cm) was recorded with inorganic fertilizer. The number of nodules was highest for vermicompost and cattle manure applications (17.16 plant-1 and 16.76 plant-1, respectively), and lowest for poultry manure (0.22 plant-1). In the R1 growth stage, poultry manure produced the highest biological fresh and dry weights, root dry weight at 25.08 g plant-1 and 5.67 g plant-1, 3.99 g plant-1 respectively. As a result, it was demonstrated that vermicompost and poultry manure applications promote strong root and plant development due to high organic matter and phosphorus and can be used successfully without inorganic fertilize application in soybean farming.